Изучение коллекционного материала озимой твердой пшеницы на наличие гена устойчивости к септориозу Stb2 - O. S. Zhogaleva; A. Yu. Myshastaya; O. S. Pavlenko; N. N. Vozhzhova; E. V. Ionova (Зерновое хозяйство России, 2020)
In order to obtain high yields of winter durum wheat, it is necessary not only to use advanced agricultural technologies, but also to sow varieties resistant to major diseases. One of these diseases that cause great harm to grain crops is Septoria leaf blotch. The current paper has presented the study results of collection material of Russian and foreign winter durum wheat according to the efficiency of the Septoria leaf blotch resistance gene Stb2 in the North Caucasus region. The purpose of the current study was to identify the Septoria leaf blotch resistance gene Stb2 in the collection material of winter durum wheat. The study was carried out in 2017–2018 in the laboratory of marker breeding of the FSBSI “ARC “Donskoy” in Zernograd. In the course of the study there have been applied such methods as the isolation of genomic DNA by the CTAB-method, PCR-analysis with the molecular SSR marker WMS533, electrophoresis on 2% agarose gel, analysis of electrophoresis gels in the Bio-Rad Image Lab 6.0 software, general data analysis by Microsoft Excel. The study has shown that 29 samples out of 185 analyzed ones had the Septoria leaf blotch resistance gene Stb2, they are the lines L3557 h42, L3182 h7, L3335 h29, L3336 h43, L3408 h218 (Russia, FSBSI “Research Center of Plants named after P. P. Lukyanenko”), K-61620 (Russia), K-54455, DF 917 (Romania), K-61924, K-59179, K-51863, K-61869 (Moldova), K-63871 (Turkey), Kharkovskaya 909 (Ukraine), MVTD-15-99 (Hungary), 2196-1/04, 922/93, 589/13, 655/13, 683/13, 145/14, 322/14, 484/14, Gordeiform 1424/82 (Russia, FSBSI “ARC “Donskoy”), Beliy Parus (Ukraine), Belgorodskaya Yantarnaya (LLC “Sativa” in Belgorod, Russia), IR named after V. Ya. Yuriev (Kharkov, Ukraine)), Zhivitsa (Russia, Prikumskaya OSS), Pandur (Romania) and Elidur (Romania). There have been recommended using the identified samples of winter durum wheat with the Septoria leaf blotch resistance gene Stb2 in breeding programs.